Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, dan Belanja Modal terhadap Tingkat Kemandirian Keuangan Daerah Provinsi Riau - Msy. Nurazania Fazria; Rita Martini; Sarikadarwati Sarikadarwati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study was conducted with the aim of analyzing how Regional Original Revenue (PAD), Balancing Funds, and Capital Expenditure affect the Level of Regional Financial Independence in Riau Province. This study takes a sample of 12 regencies/cities in the province over the period 2021 to 2023. Using a quantitative approach, this study relies on secondary data obtained through the official website of the Supreme Audit Agency of the Republic of Indonesia (www.bpk.go.id), and analyzed using the panel data regression method using Eviews software version 12. The results of data processing show that the three independent variables - namely PAD, Balance Fund, and Capital Expenditure - simultaneously have a significant influence on the level of financial independence of local governments. Individually, Local Owned Revenue contributes positively to the increase in local fiscal independence. In contrast, the Balancing Fund shows a negative correlation with the level of independence. As for Capital Expenditure, based on partial analysis, it does not show a significant impact on the level of regional financial independence in Riau Province.